A Feminist Stylistic Analysis of Ava Max’s “Kings & Queens” - Audrey, Nazzaura Kayla; Syafiq, Muhammad; Ginting, Grace Chelvia; Rangkuti, Rahmadsyah (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2026)
This research investigates the linguistic construction of feminist meanings in Ava Max's song